Absorption Mechanism of Sulfur Dioxide into Alcoholic Sodium Hydroxide Solutions (Biological Sciences - PJSIR, 2006)
The chemical absorption of sulfur dioxide into alcoholic solution of sodium hydroxide was studied by simulta- neous mass transfer and multiple instantaneous irreversible reaction. The experimental data showed the values of mass transfer enhancement factor to be much higher in the alcoholic sodium hydroxide solution. The results of present studies are compared with reversible and irreversible models over a wide range of sodium hydroxide solution concentrations, reported previously.